HUBUNGAN PERCAYA DIRI DENGAN HASIL BELAJAR PKn PESERTA DIDIK KELAS V SDN-4 PAHANDUT PALANGKA RAYA - Misyanto Misyanto (Anterior Jurnal, 2017)
This study aims to determine the relationship of confidence with the results of learning Civics students Class V SDN-4 Pahandut Even Semester Year Lesson 2016/2017. The population in this study is all students of class V in SDN-4 Pahandut in the 2016/2017 school year, amounting to 45 people. The sample of this study is the entire study population (population research). Instruments in this study are questionnaires and tests. The method used in this research is correlation method and the analysis used is Product Moment Correlation formula. Conclusion that there is a relationship Confident with Learning Outcomes Civics Students Class V SDN-4 Pahandut Palangka Raya Lesson 2012/2013. It is based on the results of data analysis is r arithmetic> r table = 0.797> 0.248 (at 5% significance level).